‘This is a Call of God … or is it?’: Narratives about Humans, God and Eschatology in the Dutch Reformed Pietist Community during the COVID-19 Outbreak - Cinjee, Tobias (Journal of empirical theology, 2021)
In this study, we examine which narratives were put forward by key figures of the Dutch reformed pietist community during the COVID-19 pandemic. We analyse sermons and news articles from the period March–November 2020. We find, as expected, a dominant narrative of COVID-19 as God’s judgment, a calling to repentance and an event which emphasizes the need for prayer. Although the pandemic was seen as a call by God, the systematic origin of the virus (God/Satan/natural phenomena) remained rather ambiguous. More often it was stated that ‘everything falls under His providence’. The earthly origin of the virus remained mostly unaddressed, as well as eschatological interpretations, contrary to our expectations. We conclude that the main narrative is a general message of repentance, rather than a concrete theological application to the dynamic of the virus, its origins and its subsequent spread. In some cases, virus ‘jargon’ even was used as a tool just to further accentuate general tendencies of reformed pietist theology.